Manual de procedimientos para la dirección de promoción recreativa regional del ICODER - Rojas-Montenegro, Ariel (Instituto Tecnológico de Costa Rica., 2016)
The ICODER is an institution created in 1998 therefore it can be considered relatively new, it is a semi-independent institution, founded under the law 7800, its main functions is the promotion and support of as much sport activities as recreational activities. The project is carried out at the Direction of Regional Recreational Promotion, which tries to promote the sport and the recreational activities at cantonal level and throughout communities. Because of the amount of regions and the amount of requests for recreational activities, a series of requirements are needed and are indispensable for the approval of them, since it is an institution of the state all documents must have the required minimal conditions because of being public and because of the financial transparency, which entails a high risk and care, reason of the necessity of establishing a strict control on the procedures and tasks carried out by the direction and therefore avoid future consequences. The present project allows through the procedures manual to maintain a better internal control of the activities, allowing the correct execution, having in mind all the regulations and the laws related to the activities executed by the Direction of Regional Recreational Promotion.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Instituto Costarricense del Deporte y la Recreación; Manuales de procedimientos; Análisis administrativo